Suicidality and Illness Course Worsening in a Male Patient with Bipolar Disorder during Tamoxifen Treatment for ER+/HER2+ Breast Cancer - Claudia Carmassi; Francesco Pardini; Valerio Dell’Oste; Annalisa Cordone; Virginia Pedrinelli; Marly Simoncini; Liliana Dell’Osso (Case Reports in Psychiatry)
Purpose. Tamoxifen is a selective estrogenic receptor modulator (SERM) drug. In addition to its common use in breast cancer ER+, Tamoxifen has been object of growing interest in psychiatry as antimanic drug. At the same time, clinical concerns about Tamoxifen’s depressogenic effect have been repeatedly raised even without reaching univocal conclusions. We discuss the case of a 45-year-old-male with a diagnosis of Bipolar Disorder type II, treated with Tamoxifen as relapse prevention treatment after surgery for a ER+/HER2+ breast cancer. The patient required two psychiatric admissions in a few-month time span since he showed a progressive worsening of both depressive and anxiety symptoms, with the onset of delusional ideas of hopelessness and failure up to suicidal thoughts. The clinical picture showed poor response to treatment trials based on various associations of mood-stabilising, antidepressants, and antipsychotic drugs. During the second hospitalization, after a multidisciplinary evaluation, the oncologists agreed on Tamoxifen discontinuation upon the severity of the psychiatric condition. The patient underwent a close oncological and psychiatric follow-up during the following 12 months. Methods. Psychiatric assessments included the Montgomery-Asberg Depression Rating Scale (MADRS), the Hamilton Depression Scale (HAM-D), the Columbia Suicide Severity Rating Scale (C-SSRS), and the Quality of Life Enjoyment and Satisfaction Questionnaire Short Form (Q-LES-Q-SF). All questionnaires were administered at the time of the second hospitalization and in a one-year follow-up. Results. Suicidal ideation fully remitted and depressive symptoms markedly and rapidly improved in the aftermath of Tamoxifen discontinuation. The symptomatological improvement remained stable across one-year follow-up. Conclusions. Male patients with a mood disorder history constitute a high-risk group as to Tamoxifen psychiatric side effects. The onset or worsening of depressive symptoms or suicidality should be carefully addressed and promptly treated, and clinicians should be encouraged to consider the possibility of discontinue or reduce Tamoxifen therapy after a multidisciplinary evaluation.